Preliminary Observations on the ‘Narrated Concerts’ of the Svete Tikhij Choir in Palermo - Rizzuto, Maria (Journal of the International Society for Orthodox Music, 2020)
The panorama of the Orthodox Churches in Sicily today is particularly relevant. Among the choirs present in Sicily, an important role has been taken by the choir of the church of St Alessandro of Comana (Moscow Patriarchate) in Palermo. The cooperation between the regent, Irina Nedoshivkina Nicotra, and the author of this abstract has given life to a concert activity structured as a dialogue with the city: these performances have been called “narrated concerts”. A narrator accompanies the audience through the ritual, through the multilingual, musical, liturgical, symbolic and spiritual aspects of the chanting. In this performance, narration and chant alternate, mutually reinforcing each other, within the broader liturgical context evoked and re-enacted by the chants performed according to the process of ritual action. The peculiarity of the choir depends on its being composed by Italians (Orthodox and Catholics) and Russians. Through the narrated, the liturgical chant expands into the city enriching the Sicilian soundscape with repertoires and executive procedures absent until ten years ago.